The Problem-Based Learning Model Integrated with The Integrated Learning Model in Science Learning: A Systematic Literature Review - Gunawan, Revi Gina; Festiyed, Festiyed; Yerimadesi, Yerimadesi; Ilwandri, Ilwandri; Gunawan, Rilla Gina (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aims to identify and analyze publications on the Problem-Based Learning (PBL) model integrated with the integrated learning model in learning Natural Sciences (IPA) based on research journal articles from 2018 to 2023. The systematic literature review method followed the PRISMA diagram. Data were obtained from 476 national and international articles through Mendeley and Google Scholar. After the screening, 15 articles that met the inclusion criteria were found as samples. The analysis showed that integrated science learning with various models effectively improves student learning outcomes. The development of modules or learning tools can also improve students' abilities and religious characters through integration at every stage of learning. Integrated science learning models such as webbed, connected, nested, and shared have been tested and proved their effectiveness in improving student learning outcomes. However, further exploration is needed regarding integrating the PBL model with the integrated learning model to implement it with better innovation. This research is expected to contribute to the development of education in the future.